Crystallization Science and Technology - Rubens Barsi Andreeta, Marcello (IntechOpen, 2012)
Crystallization is one of the most ancient and interdisciplinary topics of research known to mankind. Crystals can be organic or inorganic and may be produced from melts, liquid solutions, vapors or even in solid state. Notwithstanding its inherently high complexity, the crystallization process is part of our everyday lives, from ice making in our homes to the most state-of-the-art chemical and electronic industry. In this book, our purpose was to present new insights to the reader, as well as crucial and very useful information for researchers working in this field, while simultaneously creating a comprehensive text about crystallization processes which may serve as a starting point for people with different backgrounds.